1989
DOI: 10.1029/jc094ic03p03159
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal and interannual variability of the California Current system: A numerical model

Abstract: A reduced gravity model that incorporates the geometry of western North America has been used to study the dynamics of the California Current system. Three experiments were performed: first the model was run using 19 years of wind stress from the Comprehensive Ocean‐Atmosphere Data Set (local model); a second experiment (remote model) consisted of forcing the model through its southern boundary using the results of a similar reduced gravity equatorial model; in a third experiment, both forcings were used simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 45 publications
3
41
0
Order By: Relevance
“…The waters that detach mainly during spring/summer upwelling (Parés-Sierra and O'Brien, 1989;Simpson, 1987, 1990;Hickey, 1993;Venrick, 2000) invade the offshore stations of these two lines, modifying the temporal and spatial distribution of oceanic production. This high primary productivity calculated for line 90 during the last two cold events (1995 and 1999) has been associated with high values of the sardine spawning biomass in the southern California Current, according to CalCOFI's Figura 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The waters that detach mainly during spring/summer upwelling (Parés-Sierra and O'Brien, 1989;Simpson, 1987, 1990;Hickey, 1993;Venrick, 2000) invade the offshore stations of these two lines, modifying the temporal and spatial distribution of oceanic production. This high primary productivity calculated for line 90 during the last two cold events (1995 and 1999) has been associated with high values of the sardine spawning biomass in the southern California Current, according to CalCOFI's Figura 6.…”
Section: Discussionmentioning
confidence: 99%
“…The warm phase was recorded in 1977 and continued until 1998, increased by the 1982-83, 1992-93 and 1997-98 ENSO events that affected the California Current region (Parés-Sierra and O'Brien, 1989;Smith, 1995;Hayward et al, 1999;Moser et al, 2001;Hernández-de la Torre et al, 2003;Peterson and Schwing, 2003). The mean P T value for the autumn/winter period in ENSO years increased before the event (-1), apparantly due to the greater occurrence of nutrients in the euphotic zone; it decreased in the key year (0) and increased up to two years after (+1, +2) during the six events recorded in the time series.…”
Section: Discussionmentioning
confidence: 99%
“…During El Niñ o events, the coastal ocean of the Pacific Northwest is influenced by (i) coastally trapped waves that originate in the equatorial Pacific and propagate poleward along the west coast of the United States (Enfield and Allen 1980;Pares-Sierra and O'Brien 1989;Meyers et al 1998), (ii) enhanced poleward flows over the continental shelf and slope (Huyer and Smith 1985), and (iii) reduced coastal upwelling (Huyer et al 2002). These teleconnection patterns produce warmer than usual SSTs in the Pacific Northwest that persist for up to three seasons (Moore et al 2008a).…”
Section: Resultsmentioning
confidence: 99%
“…California Current structure thus reflects both the local winds along the west coast of North America and basinwide events within the north and equatorial Pacific Ocean. The importance of both local and remote forcing in California Current flow has been emphasized by such modeling efforts as those of Pares-Sierra and O'Brien (1989), who found that the local wind field in the northeastern Pacific is adequate to drive the annual cycle of the current system and to create the general features of its structure. They could only model interannual variations of the California Current by coupling the local model with one driven by equatorial winds.…”
Section: Dynamics Of the California Currentmentioning
confidence: 99%
“…Warm years (1958,1959) are typified by weak equatorward transport. Most of the interannual variation is coupled to El Niño−Southern Oscillation (ENSO) events in the equatorial Pacific (Pares-Sierra and O'Brien, 1989).…”
Section: Scientific Objectivesmentioning
confidence: 99%